Explaining the development-civil war relationship - Helge Holtermann (Luxembourg Income Study (LIS), 2011)
The vast majority of civil wars occur in economically less developed countries, as measured by GDP per capita. This paper assesses two suggested explanations for this: one emphasizing that poverty facilitates rebel recruitment due to lowered economic opportunity cost of rebelling, and the other highlighting that low accessibility and state capacity give political and military opportunity for organizing insurgency. I argue that the latter account is more powerful. Low accessibility is vital not only to rebel survival; it also enables rebels to obtain control over remote settlements, which facilitates the effective use of persuasion, coercion, organization, and economic rewards for mobilizing recruits and other resources. Although low economic opportunity costs can ease recruitment, it may not be essential if such tools are available. The argument is supported by a quantitative analysis covering 133 countries from 1989-2006. Countries experiencing civil war were distinguished more by low accessibility (measured by road density, telephone density and % urban of the population) than by depth of poverty (measured by the mean income of the poorest decile). Moreover, the negative association between GDP per capita and civil war risk disappeared when controlling for accessibility, but remained strong controlling for poverty.
Keywords: 330